Interfacial microstructure and mechanical properties of tungsten based powder alloy and superalloy GH907 diffusion brazing joint with Cu-Ni-V-Ti interlayer. (February 2021) - Xu, Yuxin; Qiu, Xiaoming; Wang, Suyu; Luo, Cui; Lu, Yuzhen; Xing, Fei
Abstract: Vacuum diffusion brazing of tungsten based powder alloy and superalloy GH907 was conducted using Cu-25Ni-5V-7.5Ti (wt.%) interlayer. The typical interfacial microstructure and elements diffusion behavior were characterized. Furthermore, the effect of brazing temperature and holding time on microstructure and mechanical properties of joints were also investigated. The results showed that an undulating reaction layer and a diffusion layer with the thickness of 7.2 μm were formed adjacent to the tungsten based powder alloy, indicating good metallurgical bonding. An infiltration zone with a concentration of active elements V, Ti was formed at the superalloy GH907 side. (Cu, Ni) solid solution matrix with great plasticity was observed in the interlayer, in which some Cu4 Ti3 and Ni2 V phases were distributed. The joints brazed at 1100 °C for 40min exhibited the maximum shear strength of 171.6 MPa at room temperature, and the shear strength of 113.8 MPa was maintained at the test temperature of 400 °C due to the residual V, Ti particles dispersed in (Cu, Ni) solid solution matrix. Highlights: The diffusion of V was beneficial to promote interfacial bonding. The effect of brazing temperature and holding time on microstructure and strength of the joints were investigated. The dispersed V、Ti particles were contributed to improve high temperature performance of the joints.